Role of poly-ADP-ribose polymerase inhibitors after brain progression in platinum-sensitive ovarian cancer: a case report and review of the literature - Lendinez-Sanchez, Gonzalo; Diaz-Redondo, Tamara; Iglesias-Campos, Marcos; Garrido-Almazán, Lucía; Alba-Conejo, Emilio; Rueda-Dominguez, Antonio; Sanchez-Muñoz, Alfonso (Frontiers in Oncology, 2024)
Introduction The incidence of brain metastases in ovarian cancer is quite rare, being approximately 1%–2%. According to retrospective studies, patients with BRCA 1/2 mutations present a higher risk. The trimodal approach based on surgery, radiotherapy, and chemotherapy presents better outcomes, but the prognosis remains poor with overall survival since the brain progression is around 1 year. Poly-ADP-ribose polymerase inhibitors (PARPi) have provided a new alternative for the management of advanced ovarian cancer. The SOLO2, NOVA, and ARIEL3 clinical trials do not refer data on patients with brain metastases, and the published evidence for PARPi in this setting comes only from case reports and retrospective studies. Case report We present the case of a 54-year-old woman with stage IV ovarian high-grade serous papillary carcinoma who, after 37 months of treatment with olaparib, presented a single brain lesion. After radical treatment with surgery and adjuvant whole-brain radiotherapy, she resumed olaparib with no evidence of disease during 15 months. After a second single brain relapse treated with stereotactic radiosurgery, the patient continued olaparib beyond the brain progression with no evidence of extracranial disease. Despite that there were no changes in size or number of brain lesions, the neurological situation progressively worsened and the patient died 8 months after the second progression. Discussion The higher incidence of brain metastases of ovarian cancer points out a possible tropism for the CNS in BRCA-mutated patients. In preclinical studies, PARPi has shown to cross the blood–brain barrier, with possible antitumor activity in the central nervous system (CNS) while maintaining control of extracranial disease. The best survival data are obtained with a trimodal approach, and adding a PARPi could improve the survival outcomes in the context of platinum-sensitivity disease. Targeted therapies combined with local treatments are also used in other malignancies, suggesting potential effectiveness due to tumor heterogeneity. PARPi before brain metastasis may delay its diagnosis, and using iPARP after brain metastases could improve the outcome of this population. Conclusion The role that PARPi may have in the treatment of brain metastases of ovarian cancer requires more studies. In the context of radical treatment of brain metastasis (surgery and/or RT), with no evidence of extracranial disease, maintaining treatment with PARPi beyond the brain progression should be considered.